Sound transmission using a tuning fork for the diagnosis of developmental dysplasia of the hip in newborns - Padilla-Raygoza, Nicolás; Plascencia-Roldán, Jéssica; Morales-Reyes, Guadalupe Irazú; Patiño-Gutiérrez, Luis Guillermo; Girón-Soto, Ariana Valeria; Meza-Galván, Evaristo Antonio; Anguiano-Canchola, Itzel Marcela; Luna Santillana, Sergio Emmanuel; Torres-Hernández, José Juan; Flores-Vargas, Gilberto (Frontiers in Pediatrics, 2024)
Introduction. This study aims to estimate the validity and reliability of sound transmission tests using a tuning fork and stethoscope, compared with the usual clinical procedures for the diagnosis of Developmental Dysplasia of the Hip in newborns from the state of Guanajuato, Mexico. Methodology. It is a cross-sectional study of newborns from the Guanajuato General Hospital of the Institute of Public Health from Guanajuato. The population under study comprised newborns born from April to May 2023. All parents of newborns were invited to participate. The Ortolani, Barlow, Peter-Baden, and sound transmission tests were performed with a tuning fork and stethoscope three times by two observers. Ultrasonography using the Graf technique was also applied to both hips. We evaluated the validity and repeatability of clinical procedures and sound transmission tests against ultrasonography as the gold standard. We calculated sensitivity, specificity, and predictive values for validity and Cohen's Kappa for repeatability. Results. The sample consisted of 100 newborns, 56% male and 65% born by vaginal delivery. Sound transmission tests had 87.88%, 95.81%, 80%, and 97.53% for sensitivity, specificity, positive predictive value, and negative predictive value, respectively. The intra-observer Kappa was 0.89 (95% CI=0.80-0.97) and the inter-observer Kappa was 0.85 (95% CI=0.73-0.97). The validity and repeatability of the Ortolani, Barlow, and Peter-Baden tests were low compared with the sound transmission test. Conclusion. The sound transmission test using a tuning fork and stethoscope is helpful for the diagnosis of Developmental Dysplasia of the Hip.